Tunable control of Cas12 activity promotes universal and fast one-pot nucleic acid detection - Zhou-Hua Cheng; Xi-Yan Luo; Sheng-Song Yu; Di Min; Shu-Xia Zhang; Xiao-Fan Li; Jie-Jie Chen; Dong-Feng Liu; Han-Qing Yu (Nature Communications)
Abstract The CRISPR-based detection methods have been widely applied, yet they remain limited by the non-universal nature of one-pot diagnostic approaches. Here, we report a universal one-pot fluorescent method for the detection of epidemic pathogens, delivering results within 15-20 min. This method uses heparin sodium to precisely tunes the cis-cleavage capability of Cas12 via interference with the Cas12a-crRNA binding process, thereby generating significant fluorescence due to the accumulation of isothermal amplification products. Additionally, this universal assay accommodates both classic and suboptimal PAMs, as well as various Cas12a subtypes such as LbCas12a, AsCas12a, and AapCas12b. Such a robust method demonstrates sensitivity and specificity exceeding 95% in the detection of monkeypox pseudovirus, influenza A virus, and SARS-CoV-2 from saliva or wastewater samples, when compared with qPCR or RT-qPCR. Moreover, the cost of heparin sodium per thousand uses is $0.01 to $0.04 only. Collectively, this universal and fast one-pot approach based on heparin sodium offers potential possibilities for point-of-care testing.